Celebration of Đuren in Prizrenska Gora – а Contribution to the Research - Pavlović, Aleksandar (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
In this paper the author presents several main elements of the celebration of Đuren among the Gorani in Prizrenska Gora, an event which, according to the date of the event, coincides with the celebration of Ortodox St. George’s Day. The elements of Đuren’s celebration the author tries to present taking into account its actors, and the clear spatial and temporal frameworks in which they take place. With this approach, the aim of the paper is to offer a concrete, precise presentation of the main elements of Đuren’s celebration, which could be used as an ethnographic material for repeated research of the same phenomenon and comparative monitoring of its duration and possible changes within its structure. The results presented in the paper were obtained from the field research conducted in Gorani village of Vraništa at the end of 2018 and during the celebration of Đuren in 2019.